Application of Supercontinuum Generation to Practical Absorption Spectroscopy - Filipa, Jonathan A. (My University, 2005)
Supercontinuum light generation was used as a means to generate broadband light for spectroscopic measurements. The generated broadband light was used to measure carbon monoxide (CO) absorption in a sealed laboratory test cell. This investigation served as a proof of concept for optical system development that in the future can be applied towards making combustion measurements. Some of the basic concepts underlying supercontinuum generation are reviewed and the advantages and disadvantages of this broadband light generation technique are discussed. Particularly, interference brought on by the propagation of broadband light is reviewed and methods to deal with it are discussed. The distinction between high and low quality light for making spectroscopic measurements is detailed and CO absorption measurements were made using both types of light. From reviewing the results, it was found that high quality light is superior to low quality light for making high-speed spectroscopic measurements.
Under the supervision of Assistant Professor Scott T. Sanders, Pages: 92
Keywords: University of Wisconsin--Madison. College of Engineering.; Thesis (M.S.)--University of Wisconsin--Madison, 2005.